PENGARUH BERBAGAI MEDIA PERKECAMBAHAN TERHADAP VIABILITAS DAN VIGOR BENIH TANAMAN PANGAN YANG KADALUWARSA - Nazimah (Lentera : Jurnal Ilmiah Sains, Teknologi, Ekonomi, Sosial, dan Budaya, 2021)
Food crops play an important role in ensuring the needs of energy for organisms, particularly humans. They are not only known for their economic importance, but also for their defense, security and politics aspects. This research aimed at examining the different media on viability and vigor of expired seeds, from February-March 2021 at Agroecotechnology Laboratory, Agriculture Faculty, Universitas Malikussaleh. There were 2 (two) factors observed in this study: (1) the effect of germination substrate on seed viability and vigor and (2) viability and vigor of expired seeds. The first factor examined was the seeds (B): groundnut seed (B1), paddy rice seed (B2), soybean seed (B3) and sweet corn seed. The second factor was the germination substrate: biochar (M1), rice husk (M2) and wood charcoal (M3). Completely Randomized Design was employed in this research, with replication 3 times, resulting in 36 experimental units. The results exhibited that substrate gave insignificant effect on the maximum growth, seed germination, growth uniformity and vigor index. However it significantly affected the growth rate and seed dry weight. Biochar treatments good performance in increasing the viability and vigor of expired seeds. The use of expired seeds did not influence its maximum growth, germination, growth uniformity, growth rate and vigor index, but gave significant result on seed dry weight. Seeds with good viability and vigor showed 33% of germination potency. There were no significant interaction between substrate and expired seeds on maximum growth, germination, growth uniformity, growth rate and vigor index, but had significant effect on seed dry weight.